PERAN KARAKTERISTIK KOMITE AUDIT DAN REPUTASI AUDITOR DALAM MENINGKATKAN KUALITAS AUDIT (Studi Empiris pada Perusahaan Manufaktur yang Mengganti Auditornya Secara Sukarela Tahun 2008-2011) - Komang Merawati, Luh (Buletin Studi Ekonomi, 2016)
The Role of Audit Committee Characteristic and Auditor Reputation in Audit Quality Improving. The purpose of this paper is to investigate the relationship between characteristic of audit committee (independence, financial and accounting expertise, governance expertise and activity) and auditor reputation with audit quality. The audit quality is measured based on current accrual. Population consists of Indonesian Stock Exchange listed companies from manufacturing industry in 2008 until 2011. Sample was collected based on purposive sampling and resulted in 25 companies who voluntarily switch their auditors within four years observation. Data was collected from the annual report and was analyzed with factor analysis. Hypotesis tested with multiple regression analysis. The research results found that audit committee characterictics and auditor reputation have significant effect on current accrual but in positive direction. This finding indicates that both auditor reputation and committee audit was unable to reduce current accrual and improve audit quality   Keywords: committee audit, audit quality, corporate governance
Keywords: committee audit, audit quality, corporate governance